2021
DOI: 10.1101/2021.02.03.429668
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The genomic signature of wild-to-crop introgression during the domestication of scarlet runner bean (Phaseolus coccineusL.)

Abstract: The scarlet runner bean is an open-pollinated legume from the highlands of Mesoamerica that is cultivated in small-scale agriculture for its dry seeds and immature pods. Demographic bottlenecks associated with domestication might reduce genetic diversity and facilitate the accumulation of deleterious mutations. Conversely, introgression from wild relatives could be a source of variation. Using Genotyping by Sequencing data (79,286 SNVs) from 237 cultivated and wild samples, we evaluated the demographic history… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 81 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…Some studies have confirmed that P. coccineus presents a wide variability in morpho-agronomic traits, and low to moderate levels of genetic diversity in wild and cultivated populations, being little affected by the domestication process [ 1 , 2 , 16 , 17 , 18 , 19 ]. In this sense, demographic expansion and the introgression of alleles from wild relatives are some of the factors that have increased and/or maintained the genetic diversity in cultivated populations of P. coccineus [ 20 ]. However, few studies have focused on the improvements of P. coccineus itself, and therefore there are few breeding programs focused on this species in the world, mainly in Europe [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have confirmed that P. coccineus presents a wide variability in morpho-agronomic traits, and low to moderate levels of genetic diversity in wild and cultivated populations, being little affected by the domestication process [ 1 , 2 , 16 , 17 , 18 , 19 ]. In this sense, demographic expansion and the introgression of alleles from wild relatives are some of the factors that have increased and/or maintained the genetic diversity in cultivated populations of P. coccineus [ 20 ]. However, few studies have focused on the improvements of P. coccineus itself, and therefore there are few breeding programs focused on this species in the world, mainly in Europe [ 11 ].…”
Section: Introductionmentioning
confidence: 99%